Expressão de antígenos do sistema sanguíneo ABO associados à predisposição e ao prognóstico de câncer de mama - Pozzobon, Rochele Camila Rohde (2010)
In Brazil, breast cancer (BC) is the most common malignant neoplasic diseases among women. The identification of markers that can predict the behavior of tumors is especially important, mainly due to variability in clinical disease progression. It has been a high number of new prognostic factors mentioned in literature in recent years. The inclusion of new predictors provides advances that lead to an even better selection of patients for adjuvant therapy primarily, being able to reach a better individualization of therapeutics. Many studies have shown an association between certain blood groups and different types of cancer, and have correlated the expression of antigens of the ABO blood groups in cancer cells, with more or less favorable prognosis. The purpose of this study was to evaluate the possibility of expression of antigens of the ABO blood system be applied as a marker of genetic susceptibility and / or prognosis for breast cancer and its association with other clinical prognostic factors, anatomopathological and immunohistochemical. First, through a case study (n = 127) and controls (n = 67), were analyzed the association between ABO blood type and the risk of developing breast cancer. The frequency of blood group A was significantly higher and frequency of group O significantly lower in patients with BC compared with controls. When the case study group was analyzed according to their blood group, there was a statistically significant increase in risk for BC in type A blood group patients. The results suggest that blood group type should be considered together with other factors to understand the individual risk of each patient and may be used as an independent risk marker for BC. In a second study, immunohistochemical were performed on a formalin-fixed paraffin sections of 80 tissue samples (29 benign lesions derived from breast and 51 breast carcinoma) to investigate the expression of the blood antigens A and B. There was a decrease in the tissue expression of antigen A in patients with BC, with statistical significance, assuming that the occurrence of decreased expression in malignant breast tissues can predict a more aggressive tumor behavior. No significant correlation was found between expression pattern of A and B tissue antigens in BC patients with clinical prognostic factors, anatomopathological and immunohistochemical characteristics. The distribution of the expression of antigens A and B in benign and malignant breast cells was not completely uniform. Most of the benign lesions showed maintenance of the expression of antigens, but some lost their expression, suggesting that the loss of ABO antigen expression in benign lesions may be an early marker for neoplastic transformation.